Sustainable Energy Pathways in Ageing Societies: Heterogeneous Effects of Socioeconomic and Climate Factors - Badeeb, Ramez Abubakr; Lin, Ziqing (John Wiley & Sons, 2026)
This study investigates how population ageing shapes sustainable energy pathways and introduces a novel multidimensional index to measure sustainable energy performance. The index is constructed using an entropy weighting method and measures progress across the main pillars of SDG7. It captures renewable energy expansion, energy efficiency improvements and clean energy access. Using panel quantile regression in OECD countries, the results show clear heterogeneity. The effect of ageing varies across sustainable energy performance levels and depends on socioeconomic conditions and climate vulnerability. Ageing is associated with stronger sustainable energy outcomes in high-income and climate-resilient, countries, while it constrains sustainable energy performance with high urban pressure. These findings demonstrate that demographic structure interacts with socioeconomic capacity and climate exposure in shaping sustainable energy pathways. Policies that ignore this heterogeneity risk misallocating resources. The results provide a measurement framework and distributional evidence that can support more targeted and context-specific sustainable energy transition strategies.
Keywords: Sustainable energy; ageing population; climate vulnerability; socioeconomic heterogeneity; fi=Taloustiede|en=Economics|